1976
DOI: 10.1002/lipi.19760780502
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Sheep Tail‐Fats from Five Iranian Native Breeds

Abstract: Fifteen fat samples provided from 5 sheep of 5 different Iranian native breeds were examined for their fatty acid composition by means of gaschromatography. Over 30 components could be detected in most samples. Fifteen fatty acids occurred in measurable amounts commonly higher than 0.1% up to 53.5% of the total. The saturated part consisted for the major of myristic (2.4–5.5%), pentadecanoic, (0.6–1.0%), palmitic (18.2–23.6%), heptadecanoic (0.9–2.3%), stearic (7.1–22.1%) and arachidic (0.1–0.3%) acids. Myrist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It can be observed that three broad distinctive melting endothermic peaks at ~7, ~31, and ~40°C in the first heating cycle of all the samples (Figure 6A). Although the content of LTF changes with the breed, region, and nutrition style of the animal, it mainly consists of fatty acids such as oleic, stearic, palmitic, and myristic acids 66,67 . Even our LTF consists of a mixture of these fatty acids Figure 6A shows the melting temperatures of mainly stearic (69°C‐70°C), palmitic acid (61°C‐63°C), and oleic acid (13°C‐14°C) with some melting point decrease, as it was observed as in Bond's study 68 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that three broad distinctive melting endothermic peaks at ~7, ~31, and ~40°C in the first heating cycle of all the samples (Figure 6A). Although the content of LTF changes with the breed, region, and nutrition style of the animal, it mainly consists of fatty acids such as oleic, stearic, palmitic, and myristic acids 66,67 . Even our LTF consists of a mixture of these fatty acids Figure 6A shows the melting temperatures of mainly stearic (69°C‐70°C), palmitic acid (61°C‐63°C), and oleic acid (13°C‐14°C) with some melting point decrease, as it was observed as in Bond's study 68 .…”
Section: Resultsmentioning
confidence: 99%
“…Although the content of LTF changes with the breed, region, and nutrition style of the animal, it mainly consists of fatty acids such as oleic, stearic, palmitic, and myristic acids. 66,67 Even our LTF consists of a mixture of these fatty acids Figure 6A shows the melting temperatures of mainly stearic (69 C-70 C), palmitic acid (61 C-63 C), and oleic acid (13 C-14 C) with some melting point decrease, as it was observed as in Bond's study. 68 Thus, the melting point of oleic acid decreased to $7 C and the main component stearic acid melting point decreased to 40 C while the minor component palmitic acid melting has been detected as a shoulder at $31 C. The mixture of these fatty acids solidifies at two different temperatures, one is peaking at 24 C while the other is peaking at $6 C during the cooling cycle.…”
Section: Samplesmentioning
confidence: 99%